Local fractional variational iteration method for Fokker-Planck equation on a Cantor set - Xiao-Jun Yang (Acta Universitaria, 2013)
Recently the local fractional operators have started to be considered a useful tool to deal with fractal functions defined on Cantor sets. In this paper, we consider the Fokker-Planck equation on a Cantor set derived from the fractional complex transform method. Additionally, the solution obtained is considered by using the local fractional v ariational iteration method.